Last Planner System (LPS) for Industrialized Building System (IBS) Application in Construction Industry. - Lee , Jian Heng (Universiti Teknologi PETRONAS, 2020)
Industrialised Building System (IBS) is a modern technology which can bring advancement in construction industry. Conventional construction should be replaced by IBS to meet with growing demand in the market sustainably. Malaysia government started the implementation of IBS in public sector successfully. However, IBS in the private construction sector does not. Last Planner System (LPS) is a realistic way to collaboratively manage project-based production that involves trade foremen or design team leaders (the last planners) in planning in greater and greater detail as the time for the work to be done gets closer. In this study, the Critical Success Factors (CSFs) of IBS adoption were identified using a questionnaire survey distributed among the IBS stakeholders, contractors, consultants and academician. After that, a conceptual framework was developed for adopting of IBS in Malaysia based on the LPS via Analytical Hierarchy Process (AHP) and validated through semi structured interviews. The results display importance level of each CSFs by their criteria weight according to master planning, phase planning, make-ready planning, weekly planning and learning phase in LPS.